Managing Emergencies in Rural North Queensland: The Feasibility of Teletraining - Tarsh Pandit; Robin A. Ray; Sabe Sabesan (International Journal of Telemedicine and Applications)
Introduction. Historically, the use of videoconference technologies in emergency medicine training has been limited. Whilst there are anecdotal reports of the use of teletraining for emergency medicine by rural doctors in Australia, minimal evidence exists in the literature. This paper aimed to explore the use of teletraining in the context of managing emergency presentations in rural hospitals. Methods. Using a qualitative approach, a mixture of junior and senior doctors were invited to participate in semistructured interviews. Data were transcribed and analysed line by line. Applying the grounded theory principles of open and axial coding, themes and subthemes were generated. Results. A total of 20 interviews were conducted with rural doctors, rural doctors who are medical educators, and emergency medicine specialists. Two major themes—(1) teletraining as education and (2) personal considerations—and ten subthemes were evident from the data. Most participants had some previous experience with teletraining. Access to peer teaching over videoconference was requested by rural generalist registrars. There was a preference for interactive training sessions, over didactic lectures with little mention of technical barriers to engagement. The ability of teletraining to reduce professional isolation was a major benefit for doctors practicing in remote locations. Discussion. For these rural doctors, teletraining is a feasible method of education delivery. Wider application of teletraining such as its use in peer teaching needs to be explored. The benefits of teletraining suggest that teletraining models need to be core business for health services and training providers, including specialist colleges.